Should pancreas cyst fluids be divided into two for cytological diagnosis and biochemical tests? - Şahin, Davut; Çiçek, Bahattin; Akpolat, İlkser; Şişman, Gürhan; Tekkeşin, Nilgün (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The aim of the present study was to investigate whether pancreas cyst fluids should be divided into two for cytological diagnosis and biochemical tests.Materials and Methods: The present study was conducted with fluids aspirated from 12 pancreas cysts. The fluids were divided into two and sent to the cytopathology (fluid 1) and biochemistry (fluid 2) laboratories. Fluid 1 was centrifuged at the cytopathology laboratory. Cytology slides were prepared from the deposit, and the supernatant was sent to the biochemistry laboratory. Fluid 2 was centrifuged at the biochemistry laboratory, and amylase, carcinoembryonic antigen, and cancer antigen 19.9 levels were determined in the supernatant. These procedures were repeated for fluid 1 from the cytopathology laboratory. The remaining fluid 2 was sent to the cytopathology laboratory. Fluid 1-like slides were prepared from fluid 2 in the cytopathology laboratory. Cytological diagnoses of fluid 1 and fluid 2 were compared, and the Pearson correlation coefficient for biochemical test results was identified.Results: 92% of fluid 1 and 50% of fluid 2 were diagnostic. Biochemical test results of fluid 1 and fluid 2 were similar, and the Pearson correlation coefficient was high.Conclusion: Our results showed that pancreatic cyst fluids did not need to be divided into two for cytological diagnosis and biochemical tests. Following centrifugation of the whole fluid at the cytopathology laboratory, the deposit and the supernatant can be used for cytological diagnosis and for biochemical tests, respectively. With this protocol, the sensitivity of cytological diagnoses and biochemical tests of pancreatic cyst fluids may increase.